How Riots Spread Between Cities: Introducing the Police Pathway. Issue 4 (12th October 2021) - Drury, John; Stott, Clifford; Ball, Roger; Barr, Dermot; Bell, Linda; Reicher, Stephen; Neville, Fergus
Abstract : Waves of riots are politically and psychologically significant national events. The role of police perceptions and practices in spreading unrest between cities has been neglected in previous research, even though the police are significant actors in these events. We examined the role of police interventions in the spread of rioting to one English city in August 2011 by triangulating multiple data sources and analyzing police accounts and community‐participant interviews. Rioting in other cities had relatively little direct influence in the community, but it led to heightened vigilance in the police. The resultant police mobilization inadvertently created a large gathering in a local community with a history of hostile relations with police. Police attempts to disperse the crowd affected many more people than those originally intending to riot, leading to collective conflict. These findings support a new theoretical account of the role of policing in riot spread. Complementing existing accounts of diffusion, our study helps explain how self‐fulfilling prophecy can operate to spread conflict between cities.